Pollinator diversity and soybean productivity with flowering plant (Crotalaria and Rosella). (March 2019) - Sholahuddin,; Wijayanti, R; Arniputri, R B; Supriyadi,; Widyaningrum, D
Abstract: Soybean is an important food crop in Indonesia with low productivity. Soybean production could be increased by increasing ecological services functions such as pollinator. The purpose of this study was to determine the effect of flowering plant (crotalaria and rosella) to the diversity of pollinators and their ability to enhance soybean productivity. The treatments consisted of control treatment soybean monoculture (P0), soybeans with rosella (P1), soybean with crotalaria and rosella(P2), and soybeans with crotalaria (P3). The research variables are the species and abundance of insects, insect activities, and soybean yield. The visitor flower insects consisted of Coleoptera (Coccinellidae); Hymenoptera (Apidae, Vespidae, Chalcididae, Sphecidae, Halictidae); Lepidoptera (Lycaenidae, Nymhalidae, Sesiidae) was dominated by Hymenoptera. Visitors flower insects of the soybean flower was from the family Apidae, there were Apis melifera, Xylocopa confusa, Trigona sp. The highest visiting frequency of insects in the soybean plot were in plot K3 (soybean, crotalaria and rosella). The visitors flower insects preferred the crotalaria than the rosella. Visitors flower insects which visit the crotalaria as Apis mellifera. Uncover of soybean flower could increase soybean pods. Treatment with cover got shaded and made soybean not optimal in forming pods.